Theoretical frameworks of self-efficacy in collaborative science learning practices: A systematic literature review - Reni Marlina; Hadi Suwono; I. Ibrohim; Chokchai Yuenyong; H. Husamah; H. Hamdani (University of Muhammadiyah Malang, 2024)
Theoretical framework is one of the main parts of the research paper, so that researchers are expected to be able to determine the relevant theory that underlies their research. The purpose of conducting this systematic literature review (SLR) is to review of theoretical framework, compare, and describe various theoretical research frameworks in an investigative manner on the theme of self-efficacy in collaborative science learning that underlies publications in Scopus indexed journals in the last ten years. In this regard, we used the phrase